2021
DOI: 10.1371/journal.pone.0259280
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal stability and interrelations between health behavior and subjective well-being in a follow-up of nine years

Abstract: Background The bidirectional relationship between health behavior and subjective well-being has previously been studied sparsely, and mainly for individual health behaviors and regression models. In the present study, we deepen this knowledge focusing on the four principal health behaviors and using structural equation modeling with selected covariates. Methods The follow-up data (n = 11,804) was derived from a population-based random sample of working-age Finns from two waves (2003 and 2012) of the Health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…This could be explained by the fact that covariates, as stable and independent characteristics in the observed relationships, did not substantially change during interaction in their intercourse. In line with other studies, drinking behaviors may account for interindividual differences in habits, which probably depend on the circumstances and context in which they occur, thus changing during interaction [ 22 ]. Given that drinking behaviors were not shown to have significant importance for the prediction effect of SRMH, neither in total nor in additional subgroups, this should be further examined, as well as the role of methodology and predictor selection.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This could be explained by the fact that covariates, as stable and independent characteristics in the observed relationships, did not substantially change during interaction in their intercourse. In line with other studies, drinking behaviors may account for interindividual differences in habits, which probably depend on the circumstances and context in which they occur, thus changing during interaction [ 22 ]. Given that drinking behaviors were not shown to have significant importance for the prediction effect of SRMH, neither in total nor in additional subgroups, this should be further examined, as well as the role of methodology and predictor selection.…”
Section: Discussionsupporting
confidence: 76%
“…In general, research on subjective mental health has been conducted mostly in Western nations, and studies on ethnic differences are still rare, so caution should be applied when comparing our results with other cultures [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These programmes may simultaneously increase interactions and social support 9 , possibly reducing feelings of loneliness. Stenlund et al 28 , in a longitudinal study over 9 years with adults observed a correlation between health behaviors, including PA and the subjective sensation of well-being, including a low precession of loneliness 29 .…”
Section: Discussionmentioning
confidence: 98%
“…In gerontology, life satisfaction is a concept often used to assess subjective well-being [ 12 ]; for example, a self-evaluation in the past, present, and future [ 6 ]. The measurement of subjective well-being may predict the health behavior of the elderly and contribute to the realization of healthy aging [ 13 , 14 ]. As a result, elderly SWB has received increasing attention in recent years [ 15 ].…”
Section: Introductionmentioning
confidence: 99%